STRATEGI PRIORITAS UNTUK KEBERLANJUTAN SUBSEKTOR PERKEBUNAN INDONESIA (Forum Penelitian Agro Ekonomi, 2023)
Coffee, cocoa, tea, and palm oil face challenges in international trade, including economic, environmental, and social challenges. Identifying the plantation subsector form and its forces could answer the sustainability challenges. This study used a literature review to answer three objectives. First, to identify the shape of coffee, cocoa, tea, and oil palm plantation subsector in Indonesia. Second, to evaluate the main forces that influence the subsector shape. Third, to identify priority strategies for stakeholders to better respond to sustainability challenges. The study results show that the coffee and cocoa plantation subsector are pyramid-like. In contrast, other commodities have the form of a combination of pyramids and diamonds (tea) and pyramids and inverted pyramids (palm oil). The plantation subsector shape is influenced by the interplay of various forces (i.e., production and market characteristics, enabling environment, and alternative sources of income). Thus, the strategy proposed does not work with a single instrument but a combination of various mechanisms (e.g., government policies, public and private investment, and stakeholder participation) to address challenges (as well as opportunities) according to the shapes of the subsectors and the main forces that influence them.